2006
DOI: 10.1681/asn.2006030278
|View full text |Cite
|
Sign up to set email alerts
|

Renal Bone Morphogenetic Protein-7 Protects against Diabetic Nephropathy

Abstract: Longstanding diabetes causes renal injury with early dropout of podocytes, albuminuria, glomerular and tubulointerstitial fibrosis, and progressive renal failure. The renal pathology seems to be driven, in part, by TGF-␤ and is associated with a loss of renal bone morphogenic protein-7 (BMP-7) expression. Here, the hypothesis that maintenance of renal (especially podocyte) BMP-7 by transgenic expression reduces diabetic renal injury was tested. Diabetic mice that expressed the phosphoenolpyruvate carboxykinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
254
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(272 citation statements)
references
References 23 publications
(18 reference statements)
13
254
1
3
Order By: Relevance
“…Accumulated evidence suggested that BMP-7 signaling was beneficial to resolve established organ damage, especially renal and hepatic progressive fibrosis (Wang et al 2006;Sugimoto et al 2007;Zeisberg and Kalluri 2008). Of note, small peptide agonists of BMP-7 receptors have been developed to inhibit kidney inflammation, tissue damage, and fibrosis (Sugimoto et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence suggested that BMP-7 signaling was beneficial to resolve established organ damage, especially renal and hepatic progressive fibrosis (Wang et al 2006;Sugimoto et al 2007;Zeisberg and Kalluri 2008). Of note, small peptide agonists of BMP-7 receptors have been developed to inhibit kidney inflammation, tissue damage, and fibrosis (Sugimoto et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that Grem1 levels increase during DN whereas levels of BMP-7 decrease [33,46]. Strategies that stimulate BMP-7 signalling have been shown to attenuate renal fibrosis [5,[12][13][14][15][16][17], and reductions in Grem1 levels have a similar beneficial effect in mouse models of DN [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Responding progenitor elements (stromal, periosteal, and perivascular cells) may retain their inductive response to BMPs, thereby overcoming an inhibitory environment [4]. Because BMP receptor II is downregulated in diabetes mellitus [33], it is possible treatment of a diabetic fracture with exogenous BMP may stimulate expression of BMP receptors [35]. It also is possible administration of exogenous BMP may compensate for the delay in Type X collagen expression and associated chondrocyte maturation observed in diabetes [16].…”
Section: Discussionmentioning
confidence: 99%